Penolakan Masyarakat Terhadap Pembangunan Tower Telekomunikasi di Wilayah Ilir Barat II Kota Pelembang - Syahfitri , Desta; Minako, Muchlis (Indonesian Journal of Social Development, 2023)
Analysis of the impact of the Telecommunication Tower construction is one of the studies used to identify the impact of tower construction due to changes in land use, resulting in rejection by the community which will affect the development process. The purpose of writing this research is to find out the impact of the tower and how the construction process will go if the community refuses. In the area of Jalan Ki Gede Ing Suro Rt 28 Kel 32 Ilir Palembang, The research method used in this study is a qualitative research method. Qualitative research is used to understand the context of research by describing in detail and depth related to the conditions experienced by a context as well as what is happening in the field.